동작 인식 기반 유아용 인터랙티브 에듀테인먼트 콘텐츠 제작 플랫폼 - 남상훈(SangHun Nam); 이지용(JiYong Lee); 고기남(Ginam Ko); 서규원(KyooWon Suh) (디지털콘텐츠학회논문지, 2019)
유아들의 신체활동 놀이는 신체발달과 창의적인 상상력을 계발에도 도움을 준다고 연구되고 있기 때문에, 유아의 움직임을 통한 적절한 교육방법을 연구한다면 효과적인 교육 콘텐츠를 개발할 수 있을 것이다. 본 연구에서는 교사들의 아이디어를 적용하여 쉽게 새로운 교육 콘텐츠를 제작할 수 있는 에듀테인먼트 콘텐츠 제작 플랫폼에 관한 연구를 수행하였다. 교사들이 유아들의 움직임에 반응하는 아이콘의 이미지, 경로 애니메이션, 접촉 시 나타나는 효과와 음향을 쉽게 설계할 수 있다. 교사들은 직접 설계한 교육 콘텐츠를 유아들에게 활용하고 반응을 분석하며 인터랙티브 에듀테인먼트 콘텐츠를 반복적으로 수정하며 발전시킬 수 있다. Children's physical activity play also helps to develop physical development and creative imagination, so if a teacher research the appropriate educational method through the movement of the infant, effective educational contents can be developed that can develop physical development and creativity at the same time. In this study, we conducted a study on the edutainment contents production platform that can easily create educational contents by applying the ideas of teachers. Teachers can easily design educational content by setting images of the icons that respond to children’s movements, path animations, and the effects and sounds of contact. Teachers can use their own educational content for infants, analyze their response, and revise interactive edutainment content. KCI Citation Count: 5